Does it Pay to Be a Cadre? Estimating the Returns to Being a Local Official in Rural China - Zhang, Jian (The World Bank, 2012)
Recruiting and retaining leaders and public servants at the grass-roots level in developing countries creates a potential tension between providing sufficient returns to attract talent and limiting the scope for excessive rent-seeking behavior. In China, researchers have frequently argued that village cadres, who are the lowest level of administrators in rural areas, exploit personal political status for economic gain. Much existing research, however, compares the earnings of cadre and non-cadre households in rural China without controlling for unobserved dimensions of ability that are also correlated with success as entrepreneurs or in non-agricultural activities. The findings of this paper suggest a measurable return to cadre status, but the magnitudes are not large and provide only a modest incentive to participate in village-level government. The paper does not find evidence that households of village cadres earn significant rents from having a family member who is a cadre. Given the increasing returns to non-agricultural employment since China's economic reforms began, it is not surprising that the returns to working as a village cadre have also increased over time. Returns to cadre-status are derived both from direct compensation and subsidies for cadres and indirectly through returns earned in off-farm employment from businesses and economic activities managed by villages